2019
DOI: 10.1128/jb.00244-19
|View full text |Cite
|
Sign up to set email alerts
|

cyAbrB Transcriptional Regulators as Safety Devices To Inhibit Heterocyst Differentiation in Anabaena sp. Strain PCC 7120

Abstract: Cyanobacteria are monophyletic organisms that perform oxygenic photosynthesis. While they exhibit great diversity, they have a common set of genes. However, the essentiality of them for viability has hampered the elucidation of their functions. One example of these genes is cyabrB1 (also known as calA in Anabaena sp. strain PCC 7120), encoding a transcriptional regulator. In the present study, we investigated the function of calA/cyabrB1 in the heterocyst-forming cyanobacterium Anabaena sp. PCC 7120 through CR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…cyABrB1 (calA) is one such regulator that inhibits the heterocyst formation. It is observed that the conditional knockdown of cyABrB1, using CRISPR interference, leads to the formation of heterocyst, even in the presence of nitrate [8]. It is found that the knockdown of cyABrB1 leads to the upregulation of hetP and hepA (promoters of heterocyst differentiation), which are otherwise induced by HetR.…”
Section: Heterocyst Differentiation Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cyABrB1 (calA) is one such regulator that inhibits the heterocyst formation. It is observed that the conditional knockdown of cyABrB1, using CRISPR interference, leads to the formation of heterocyst, even in the presence of nitrate [8]. It is found that the knockdown of cyABrB1 leads to the upregulation of hetP and hepA (promoters of heterocyst differentiation), which are otherwise induced by HetR.…”
Section: Heterocyst Differentiation Inductionmentioning
confidence: 99%
“…It is found that the knockdown of cyABrB1 leads to the upregulation of hetP and hepA (promoters of heterocyst differentiation), which are otherwise induced by HetR. It is proposed that the ratio of HetR and cyABrB1 might be playing an important role in the commitment of vegetative cells toward heterocyst formation [8]. Likewise, PknE kinase (alr3732) is also known to inhibit HetR during a later stage in differentiation [9].…”
Section: Heterocyst Differentiation Inductionmentioning
confidence: 99%
“…Higo et al used the CRISPRi approach to switch the expression of calA to a level low enough to obtain some phenotypes (3). Unfortunately, the authors could not confirm the essential function of calA, as one would expect, albeit the growth of the corresponding mutant under interference conditions was significantly inhibited.…”
mentioning
confidence: 99%
“…At least two direct targets of CalA are identified, hetP and hepA, as CalA can bind to their promoter regions (3). The expression of these two genes is increased once calA expression is turned down, and this regulation is independent of HetR.…”
mentioning
confidence: 99%
See 1 more Smart Citation